Study of hydrodynamic-tunnelling effects induced by high-energy proton beams in graphite. Issue 1 (1st January 2023) - Wiesner, C; Carra, F; Don, J; Kolthoff, I; Lechner, A; Rasile, R; Wollmann, D
Abstract: The design and assessment of machine-protection systems for existing and future high-energy accelerators comprises the study of accidental beam impact on machine elements. In case of a direct impact of a large number of high-energy particle bunches in one location, the damage range in the material is significantly increased due to an effect known as hydrodynamic tunnelling. The effect is caused by the beam-induced reduction of the material density along the beam trajectory, which allows subsequent bunches to penetrate deeper into the target. The assessment of the damage range requires the sequential coupling of an energy-deposition code, like FLUKA, and a hydrodynamic code, like Autodyn. The paper presents the simulations performed for the impact of the nominal LHC beam at 7 TeV on a graphite target. It describes the optimisation of the simulation setup and the required coupling workflow. The resulting energy deposition and the evolution of the target density are discussed.